PENGARUH EDUKASI MEDIA PUZZLE TERHADAP MINAT BELAJAR MATEMATIKA SISWA KELAS III SEKOLAH DASAR NEGERI 36 PALEMBANG - Soleha, Ayu; Masagus Firdaus; Yusni Arni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the effect of puzzle media on the interest in learning mathematics of grade III students at State Elementary School 36 Palembang in the even semester of the 2024/2025 academic year. The objects of this study were 40 grade III students. This study applied an experimental method with an experimental class that received treatment using puzzle media and a control class that applied conventional methods. Information was obtained through initial tests (pretest) and final tests (posttest) using questionnaires and basic questions. The results of the descriptive statistical analysis indicated that the average value of learning interest in the experimental group increased from 63.50 (pretest) to 83.35 (posttest), while the control group only increased from 65.00 (pretest) to 70.10 (posttest). The Shapiro-Wilk normality test showed that all data, both pretest and posttest in both groups, were normally distributed (Sig. value> 0.05). The Levene's Test homogeneity test also showed that the data variance was consistent (Sig. value> 0.05). Hypothesis testing with Paired Samples T-Test in the experimental group showed a significant difference between the pretest and posttest scores (Sig. 0.000 <0.05). Meanwhile, the Independent Sample T-Test comparing the posttests of the two groups showed a significant difference with a significance value of 0.000 (p <0.05), where the posttest score of the experimental group was significantly higher. Thus, it can be concluded that the use of puzzle media has a positive and significant impact on increasing the interest in learning mathematics of grade III students at State Elementary School 36 Palembang compared to learning without using media. Puzzle media has proven effective in attracting students' interest, training logical thinking skills, counting skills, and creating a fun learning environment.